2021
DOI: 10.48550/arxiv.2104.12653
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

I am Definitely Manipulated, Even When I am Aware of it. It s Ridiculous! -- Dark Patterns from the End-User Perspective

Kerstin Bongard-Blanchy,
Arianna Rossi,
Salvador Rivas
et al.

Abstract: Online services pervasively employ manipulative designs (i.e., dark patterns) to influence users to purchase goods and subscriptions, spend more time on-site, or mindlessly accept the harvesting of their personal data. To protect users from the lure of such designs, we asked: are users aware of the presence of dark patterns? If so, are they able to resist them? By surveying 406 individuals, we found that they are generally aware of the influence that manipulative designs can exert on their online behaviour. Ho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…In opposition to rational persuasion, manipulation refers to subverting the manipulee's vulnerabilities in a hidden way [35,36]. To resist this influence, prior work has shown that it is necessary to perceive the try of subversion and have agency over it [2,3,23,27]. Therefore, it is first necessary to understand the users' vulnerabilities towards user interfaces to analyse if they are manipulated or not and, second, test their capability to resist it.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In opposition to rational persuasion, manipulation refers to subverting the manipulee's vulnerabilities in a hidden way [35,36]. To resist this influence, prior work has shown that it is necessary to perceive the try of subversion and have agency over it [2,3,23,27]. Therefore, it is first necessary to understand the users' vulnerabilities towards user interfaces to analyse if they are manipulated or not and, second, test their capability to resist it.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, although the literature on awareness and detection of dark patterns is increasing, the effects these mechanisms have on vulnerable populations -children, the elderly, lower digitally skilled users, and minorities-are under-explored. Bongard-Blanchy et al [2] and Luguri and Strahilevitz [20] have found manipulative design to be more impactful on users with a lower education level, hinting at a problem that is urgent to address.…”
Section: Related Workmentioning
confidence: 99%